TMP269, a small molecule inhibitor of class IIa HDAC, suppresses RABV replication in vitro - Yin, Juanbin; Wang, Shasha; Ren, Shanhui; Liang, Zhengji; Ge, Junwei; Sun, Yuefeng; Yin, Xiangping; Wang, Xiangwei (Frontiers in Microbiology, 2023)
TMP269, a novel selective class IIa histone deacetylase inhibitor, plays an important role in cancer therapeutic. However, the effect of TMP269 on regulation viral replication has not been studied. In the present study, we found that TMP269 treatment significantly inhibited RABV replication at concentrations without significant cytotoxicity in a dose-dependent manner. In addition, TMP269 can reduce the viral titers and protein levels of RABV at an early stage in the viral life cycle.RNA-sequencing data revealed that immune-related pathways and autophagy-related genes were significantly downregulated after RABV infection treated with TMP269.Further exploration shows that autophagy enhances RABV replication in HEK-293T cells, while TMP269 can inhibit the autophagy to decrease RABV replication. All together, these results provide a novel treatment strategy for rabies.